Effects of jump height on forelimb landing forces in border collies - Pogue, Joanna; Zink, Chris; Kieves, Nina R. (Frontiers in Veterinary Science, 2022)
Objective The objective of this study was to evaluate the effects of jump height on the landing forces of dogs. Animals Client-owned Border Collies experienced in agility competition, n = 9. Procedures The study involved client owned border collies with the same AKC standard jump height of 20 inches and preferred height of 16 inches. Standard height is based upon the height of the dog at the withers, with preferred height referred to as reduction in jump height by one level due to injury or age. An AKC regulation bar jump was placed over a previously validated pressure sensitive walkway (PSW). The peak force (%BW) and peak contact pressure (kPa) of the leading and trailing forelimbs were evaluated for all dogs. Results There was no significant difference in landing force between the two jump heights for either peak force as a percentage of body weight or peak contact pressure when evaluated in both leading and trailing forelimbs. Conclusions and clinical relevance Our findings demonstrated no significant difference in active landing forces of peak contact pressure and peak force on the forelimbs of dogs when jumping at a standard jump height vs. a preferred jump height when controlling for velocity in dogs performing a single running bar jump. These results suggest that the recommendation of decreasing jump height for older animals or injured animals may not provide a significant decrease in the impact on the forelimbs. It is likely that other factors contribute to the total forelimb kinematics picture during competition. Veterinarians and trainers should consider additional ways to decrease impact for canine athletes as they recover from injury.